Pengaruh Kualitas Produk, Customer Bonding dan Kepuasaan Pelanggan Terhadap Kesetiaan Pelanggan (Studi Kasus Pada Pelanggan Clodia Outfit) - Faliddah Mukadar; Agus Widarko; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine and explain the effect of product quality, customer bonding and customer satisfaction on customer loyalty (a case study on Clodia Outfit customers). The population in this study were customers who had made a purchase at Clodia Outfit. The sample used the Malhotra theory so that 90 respondents were obtained according to the criteria, the research method used purposive sampling with a quantitative approach. This study uses primary data and multiple linear regression analysis methods.The results showed that simultaneously had a positive and significant effect on product quality, customer bonding and customer satisfaction variables on customer loyalty. And partially the product quality variable has no and no significant effect on customer loyalty, the customer bonding variable has a positive and significant effect on customer loyalty and the customer satisfaction variable has no and no significant effect on customer loyalty. Keywords: Product Quality, Customer Bonding, Customer Satisfaction, Customer Loyalty